O controle concentrado de constitucionalidade e a ação direta de constitucionalidade 48 - Diehl, Leonardo José (2024)
The purpose of this study is to evaluate the decision made by the STF in Direct Action of Constitutionality No. 48, which ruled that Law 11,442/2007 was constitutional, regarding the characterization of the contract of the Independent Cargo Transporter (TAC) as a commercial relationship without the possibility of recognizing the employment relationship. The main objective of the Concentrated Control of Constitutionality is to promote the guarantee and enforcement of the rights provided for in the Brazilian Federal Constitution, among them, the guarantees directed to workers. However, the aforementioned decision prevents access to these rights by a significant portion of workers in the road freight transportation sector. The aim is to examine possible solutions to the problem, analyzing the adequacy of ADC 48 to the objectives of Concentrated Control of Constitutionality. To this end, a historical analysis of the importance of Constitutionalism and the objectives of Concentrated Control of Constitutionality is made, in comparison with the decision handed down in the aforementioned ADC.